Strengthening Reading, Writing, and Numeracy Literacy through Integrated Thematic Learning for Students in the Elementary School Teacher Education - Rivaldo Paul Telussa; Santji Afi Rangkoly; Jasmari; Tut Hidayatillah; Jermanto Subeno Lasamahu (CV. TOTUS TUUS, 2026)
This community service program was conducted in response to the need to strengthen integrated literacy and numeracy competencies among preservice elementary school teachers. The purpose of this study was to enhance students’ reading–writing literacy and numeracy skills through the implementation of integrated thematic learning in the Elementary School Teacher Education Program (PGSD) at Universitas Satya Wiyata Mandala. The method employed was a participatory and reflective community service approach, implemented through thematic learning workshops, guided practice, mentoring, and continuous reflection activities. Participants were actively involved in critical reading, reflective writing, and contextual numeracy problem-solving embedded within thematic learning activities relevant to elementary education. Data were collected through observation, literacy and numeracy assessments, student response questionnaires, and documentation, and analyzed descriptively using qualitative and simple quantitative techniques. The findings indicate that the implementation of integrated thematic learning effectively improved students’ ability to connect reading, writing, and numeracy skills in a meaningful and contextual manner. In addition, students demonstrated increased pedagogical awareness, confidence, and readiness to design thematic learning activities that integrate literacy and numeracy for elementary classrooms. Overall, the program successfully achieved its objectives and shows strong potential for sustainable implementation in preservice teacher education to support the development of competent and reflective future elementary school teachers.